Enantioselective Reduction of α‐Cyano and α‐Nitro Substituted Acetophenones Promoted by a Bifunctional Mesoporous Silica. Issue 10 (28th June 2013) - Deng, Boxin; Cheng, Tanyu; Wu, Meng; Wang, Jinyu; Liu, Guohua
<x xml:space="preserve">Abstract</x> Pores that put your reaction in a spin! A recoverable mesoporous silica exhibits excellent catalytic activity and enhanced enantioselectivity for the reduction of α‐cyano and α‐cyanoacetophenones that ascribes the synergistic effect of its phase‐transfer functionalized cetyltrimethylammonium bromide and confined chiral organoiridium catalytic nature.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>